2022
DOI: 10.1186/s12877-022-03265-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between testosterone and serum soluble α-klotho in U.S. males: a cross-sectional study

Abstract: Purpose Testosterone plays a crucial role in males, and the deficiency of testosterone leads to multiple adverse health conditions. Klotho is a recently discovered protein encoded by antiaging gene klotho. Both the levels of testosterone and klotho change with aging, so the relationship between them is worth exploring. The purpose of this study was to investigate whether total testosterone is associated with serum klotho levels in U.S. males aged 40–79 years. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…Recent studies show no significant difference between the levels of soluble Klotho in the serum, 73 though high testosterone has also been associated with high soluble Klotho levels. 74 The disparities might be caused by different assays used to measure serum Klotho.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show no significant difference between the levels of soluble Klotho in the serum, 73 though high testosterone has also been associated with high soluble Klotho levels. 74 The disparities might be caused by different assays used to measure serum Klotho.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Our stratified analysis found that low levels of serum Klotho were associated with a higher risk of developing anemia more significantly in men and diabetic patients. A study using a sample of 3750 men aged 40-79 years in the USA found a positive correlation between total testosterone and S-Klotho levels [ 20 ]. The role of androgens in stimulating erythropoiesis has been well established since the 20th century, and the testosterone produced by the testes is the main circulating androgen in men.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of m-KL tend to be female-dominant throughout life, [54][55][56] while estrogen, testosterone, and sexual hormone binding protein (SHBG) were all positively correlated with serum m-KL also in men. 57 Besides, there is strong evidence for a mediating role of estrogen in the m-KLinduced inhibition of NaPT-II, causing enhanced excretion of PO4and iAsV. 58,59 Contrary results with age-associated increased %iAs and decreased %DMA in a smaller study population of an arseniasis-hyperendemic area in Taiwan suggest possible regional differences in the age-dependency of TWuAs composition.…”
Section: Influence Of Age On Renal Arsenic Excretionmentioning
confidence: 99%